Synthesis of 1, 4- Dihydropyrano [2, 3-c] pyrazole Derivatives with no Catalyst Under Ultrasound Irradiation - Wang Shu-Xiang; Wang Wei; Li Ji-Tai (E-Journal of Chemistry)
A series of 6-amino-4-aryl-5-cyano-3-methyl-1-phenyl-1, 4-dihydropyrano [2, 3-c]pyrazoles were synthesized in 84%-95% yields by the condensation of aromatic aldehydes, malononitrile with 3-methyl-1-phenyl-2-pyrazolin -5-one with no catalyst under ultrasound irradiation.